Expansão, interiorização e democratização de acesso a educação superior pública : o caso da Unipampa - Gentil, Viviane Kanitz (2017)
The main objective of this study is to understand and analyze the education policy that expanded public higher education in Brazil by founding new public universities in small towns and by democratizing access to public higher education. Our focus is on the process of establishing the Federal University of the Pampa (Universidade Federal do Pampa) — Unipampa, between 2005 and 2008, which resulted from a federal government’s higher education expansion program (Programa Expandir). We start by presenting a theoretical analysis of the history of higher education in Brazil, Brazilian public education policy, and the expansion of public higher education over the last decades. Our empirical investigation involved the analysis of various documents, as well as interviews with institutional and political leaders, and with academic and administrative staff at Unipampa. Participants revealed their own views and expectations towards the creation of a new university as a result of the implementation of a public policy entwined with local political and social movements which aimed at the democratization of higher education. We analyze the process of establishment of the new university, taking into consideration the guidelines of the public policy for higher education expansion, under Luiz Inácio Lula da Silva's administration, in the light of the contexts of influence, text production and practice, presented in Ball and Bowe’s policy cycle (1992) and detailed by Mainardes (1996). Our research findings reveal that the foundation of Unipampa generated substantial political clout, aligned with a significant social movement which resulted in government actions in favor of the southern boarder of Brazil, where the university is located. The development of the new university was conducted by a consortium of two federal universities responsible for structuring and tutoring Unipampa until its oficial foundation in 2008 (Federal Law no 11.640). The process was based on the principles of the federal government’s higher education expansion program, which stipulated efective participation of civil society and local government in the structuring of new higher education institutions. This, however, did not minimize the initial difficulties, especially in terms of infrastructure and academic, administrative and organizational development. In 2007, after creating a commission for the establishment of Unipampa, difficulties were progressively overcome, and the university was restructured and consolidated by planning and implementing management strategies aimed at the constitution of identity of the new institution. The process was directly influenced by those involved in the efective implementation of the federal government's policy which resulted in the foundation of Unipampa. In sum, this study clearly points out the importance of the federal government's public policies as key contributors to the expansion of higher education, the creation of new public small-town universities and the democratization of access to higher education in Brazil. Besides, the establishment of Unipampa opened the door to local development, creating a new reality to young people and adults, who finally have access to higher education thanks to the foundation of a public university in their own town.